Changes in ginsenoside patterns of red ginseng extracts according to manufacturing and storage conditions - Lee, Seon-Ho (Food Sci Biotechnol, 2017)
Although the pharmacological action of red ginseng is mostly generated by ginsenosides, contents of ginsenosides in manufactured extracts are still varying according to processing and storage conditions. Rg1, Rb1, and Rh1 levels significantly decreased overtime under pH adjustment and thermal treatment during storage, and these changes were exacerbated at lower pH and higher storage temperature. However, Rg3 level showed the opposite pattern compared to other ginsenosides. Rg3 level linearly increased at higher temperature and pH while significantly decreased at pH 2. Furthermore, Rg3 level constantly increased during storage. This is the first combined study on the effects of manufacturing and storage conditions on ginsenoside contents of red-ginseng-extract products. To minimize loss of major marker and bioactive compounds of red ginseng products during manufacturing processes and storage, it is recommended that red-ginseng-extracts be maintained at pH 6–8, sterilized at below 105 °C, and stored at below 25 °C.